Service-oriented design of microfludic devices - Panikowska, Katarzyna E. (Cranfield University, 2011)
Microfluidics is a relatively new and, with an estimation of the market for these devices exceeding $ 3 billion in 2014, it is considered a profitable domain. Constant development of new technologies and growing demand for more versatile products cause increasing complexity in this area. To address this, the current trends for the domain include automation, standardisation and customisation. At the same time, the society is moving from product types offering to services. Due to the customisation trend this transition appears beneficial for microfluidics. Taking advantage of these opportunities, an investigation of microfluidic design has been undertaken to address the issues at their origins. The literature review showed a lack of a general design methodology applicable for all microfluidic devices, identified existing approaches as technology driven and the domain as unique in terms of design. Also, it highlighted a number of automation and standardisation attempts in the area. In addition, microfluidics shows limited customer and service-orientation. Meanwhile, an investigation of complexity and its implications in microfluidics narrowed the study to sub-section interactions, which allowed standardisation and automation without compromising customisation. In response to these gaps, an aim of the research is to develop a guideline for service- oriented design of microfluidic devices that can deal with sub-section interactions. This research reviews: existing methodologies for design in micro-scale, their applicability to the domain, microfluidic practitioners’ approach to design, state of service-thinking and services in the area and how sub-section interactions are dealt with for these devices. The developed guideline and design enablers present a proposal for a general process for the design of microfluidics. The solution attempts to tackle the issue of sub- section interactions and brings the domain one step towards an ‘experience economy’ by incorporating service-considerations into the design process. The usefulness of this contribution has been confirmed by a variety of methods and numerous sources including experts in the field.